ANALYSIS AND QUANTIFICATION OF WATER EROSION IN NORTHERN ALGERIAN WATERSHEDS - BELLOUT, Mahieddine; BOUTOUTAOU, Djamel (GeoScience Engineering, 2024)
Algeria is characterized by a semi-arid climate, particularly vulnerable to erosion of agricultural land, where physical, hydroclimatic, geomorphological and socio-economic conditions are highly favourable to the onset and acceleration of this phenomenon. High concentrations of suspended sediments transported by rivers to dams and reservoirs represent a significant problem for water management and the sustainability of these infrastructures. During this study, solid transport data were collected from the Agence Nationale des Ressources Hydrauliques database. The data set includes a total of 132 hydrometric stations throughout the country. Exploiting pairs of instantaneous liquid flow measurements (m³/s) and instantaneous solid flow measurements (kg/s) has led to the establishment of regressions at different time scales, thus concluding that the power model is the most appropriate based on the coefficient of determination R². The average annual specific erosion varies from one watershed to another, generally between 11,75 and 5978,34 T/km².year. The principal component analysis (PCA) method was used to study the average monthly solid discharges of 132 hydrometric stations, and the results obtained highlight the presence of four hydrologically homogeneous groups. Multiple regression was performed on the four groups to highlight a potential relationship between the dependent variable, specific erosion, and other explanatory variables. The correlations indicate that each group is influenced by parameters distinct from the others, as in the case of group A, where the correlations between specific erosion, on the one hand, and the other hand, the Average slope of a watershed (Im), lithology index (IL), runoff coefficient (RC), and the normalized difference vegetation index (NDVI) are significant.